2021
DOI: 10.3390/en14040870
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Thermal Characteristics and Microstructure/Composition of Carbon Dioxide Hydrate in the Presence of Cyclopentane

Abstract: Hydrate-based carbon dioxide (CO2) separation and capture is a new technology for achieving CO2 emission reduction. However, it is still not commercially applied for the ambiguity of microscopic hydrate formation mechanism. In a constant volume experiment of hydrate formation, there are two or more pressure platforms, indicating that there might be two or more different hydrates formation in succession. In order to reveal the relationship between the microscopic process and the gas consumption in the process o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Rodger [32] believed that the memory effect of methane hydrate is caused by the high concentration of methane in the solution due to the slow diffusion of methane after dissociation. Similarly, Zhang [30] studied the dissolution properties of CO 2 throughout the induction time and concluded that the 'memory effect' of hydrate should not be attributed to the residual structure. Instead, the residual gas molecules in the aqueous solution and the gas concentration are the key factors in hydrate nucleation.…”
Section: Mnbs Reinforce Hydrate Formation With Memory Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodger [32] believed that the memory effect of methane hydrate is caused by the high concentration of methane in the solution due to the slow diffusion of methane after dissociation. Similarly, Zhang [30] studied the dissolution properties of CO 2 throughout the induction time and concluded that the 'memory effect' of hydrate should not be attributed to the residual structure. Instead, the residual gas molecules in the aqueous solution and the gas concentration are the key factors in hydrate nucleation.…”
Section: Mnbs Reinforce Hydrate Formation With Memory Effectmentioning
confidence: 99%
“…In addition, mechanical stirring is complex and challenging to apply on a large scale at high pressure and low temperature. Additives (including sodium dodecyl sulfate (SDS) [22,23], tetrabutylammonium bromide (TBAB) [24,25], tetrahydrofuran (THF) [26,27], cyclopentane (CP) [28][29][30], etc.) introduce impurities and disrupt the hydrate reaction system, which is Processes 2023, 11, 1019 2 of 15 not ideal for reinforcement effects.…”
Section: Introductionmentioning
confidence: 99%